Non-Pharmaceutical Intervention Policies in Overcoming COVID-19 in Aceh: A Cross-Sectional Online Survey - Saddam Rassanjani; Aryos Nivada; Ratnalia Indriasari; Iqbal Ahmady (Universitas Muhammadiyah Tangerang, 2022)
ABSTRACTCOVID-19, which transmitted rapidly from China, has crossed all the lands in the world, infecting people in every corner. This phenomenon has shocked the public on a large scale, ranging from the mass media; government; to individuals. This study seeks to assess the perceptions of the Acehnese regarding government policy in dealing with COVID-19 in the local realm, especially related to the implementation of non-pharmaceutical interventions (NPIs). An online survey was conducted using a semi-structured questionnaire using a non-probability snowball sampling technique to answer the abovementioned problem. Finally, the questionnaire distributed online collected as many as 264 respondents. In general, the results of the study report that respondents have a high level of compliance with the policies taken by the government in fighting the Coronavirus. Most of them claim to be ready to help their neighbors who have problems with loss of livelihood during the implementation of NPIs that require people to work at home. Interestingly, even though the community has shown willingness to follow government guidelines on quarantine and social distance, most people reject the call to worship at home. Therefore, in formulating the best policy, a comprehensive socio-economic study and cooperation from community leaders, especially religious leaders, are needed to equalize the public’s perception. Keywords: Non-pharmaceutical intervention, public policy, Covid-19, Aceh ABSTRAKCOVID-19 yang menular dengan cepat dari Cina telah melintasi seluruh daratan di dunia, menjangkiti manusia di setiap sudut. Fenomena ini telah menghebohkan publik secara besar-besaran, mulai dari media, pemerintah, hingga individu. Kajian ini berupaya mengkaji persepsi masyarakat Aceh mengenai kebijakan pemerintah dalam menangani COVID-19 di ranah lokal, khususnya terkait penerapan intervensi nonfarmasi (NPIs). Untuk menjawabnya, dilakukan survei online dengan menggunakan kuesioner semi terstruktur dengan teknik non-probability snowball sampling, dan akhirnya berhasil mengumpulkan sebanyak 264 tanggapan. Secara umum responden memiliki tingkat kepatuhan yang tinggi terhadap kebijakan yang diambil pemerintah dalam memerangi virus corona. Sebagian besar dari mereka mengaku siap membantu tetangganya yang bermasalah dengan hilangnya mata pencaharian selama penerapan NPIs. Menariknya, meski masyarakat telah menunjukkan kesediaan untuk mengikuti pedoman pemerintah tentang karantina dan menjaga jarak, kebanyakan orang menolak ajakan untuk beribadah di rumah masing-masing. Oleh karena itu, dalam merumuskan kebijakan yang terbaik, diperlukan kajian sosial ekonomi yang komprehensif dan kerjasama dari tokoh masyarakat, khususnya tokoh agama, untuk menyamakan persepsi masyarakat. Kata Kunci: Non-pharmaceutical intervention, kebijakan publik, Covid-19, Aceh